KAJIAN ORNAMEN GORGA DI RUMAH ADAT BATAK TOBA (Studi Kasus : Di Kawasan Desa Wisata Tomok, Huta Siallagan dan Huta Bolon Di Kabupaten Samosir) - Saragih, Dearma A; Yulianto, Yulianto; Pakpahan, Raimundus (Unika Santo Thomas, 2019)
One of the interesting cultural potentials to be studied is traditional houses. This traditional house has its own uniqueness in every area. One of the uniqueness can be seen from the many ornaments in it. Diversity has its own meaning and function. Ornaments is one of the historical heritage of Indonesia where almost all the tribes in Indonesia can be found various kinds of ornaments that reflect the techniques of each region in Indonesia. Ornament Batak Toba is one of the many ornaments that exist in this country Indonesia. Toba Batak ornament can be found in North Sumatera Province precisely in Samosir regency which always apply Toba Batak ornament as decoration or as identity in important building for Batak Toba, for example in traditional house building in Huta Siallagan, Tomok Village and Huta Bolon.This research is classified in research using descriptive-comparative research method, doing the study by comparing the existing ornaments in these three villages with theories about Ornaments Gorga Rumah Adat Batak Toba, then do the analysis of the condition in accordance with the theory used as a reference